Feasibility Analysis of Bustier and Peplum with Puzzle Shape Patchwork Technique - Fahira, Jian; Prasetyaningtyas, Wulansari (Universitas Negeri Semarang, 2026)
The development of fashion trends influenced by technology and social media has increased fashion consumption among the public, especially teenagers. The rise of fast fashion accelerates the trend cycle while contributing to the increasing volume of patchwork waste. This condition encourages design innovation that supports sustainable fashion. This study aims to explain the process of making and analyzing the feasibility of bustier and peplum using a puzzle-shaped patchwork technique by utilizing batik patchwork fabric waste from a production house in the Sekaran area, Gunungpati. The research method uses a quantitative descriptive approach with data collection techniques using observation sheets. The research instrument was tested for validity using the Aiken's Coefficient V with the validity results of 30 assessment items having a V value of ≥ 0.75 and stating that all items are valid. The reliability test used intraclass correlation coefficient (ICC) with a single measure value of 0.926, and an average measure of 0.978, showing very good reliability. The data analysis in this study uses percentage descriptive analysis to produce quantitative data. The results of the study show that; 1) The making of bustiers and peplums begins with a moodboard and design that is used as a reference, then the manufacturing process is carried out gradually and systematically, starting from the determination of tools and materials, pattern making, sewing process, and final finishing; 2) The results of the feasibility analysis based on the assessment of 5 expert panelists and 20 trained panelists on six indicators show that the category is very feasible with The overall percentage is 94%, with the assessment results of each indicator, namely design of 16.07%, speciality of 16.02%, aesthetics of 15.73%, fashion performance of 15.60%, size of 15.52%, and sewing technique of 15.37%, which as a whole show good assessment results.